LEECH’S POLITENESS PRINCIPLE IN LENONG BETAWI HUMOROUS DIALOGUE ENTITLED “ANAK DURHAKA” - Ninuk Lustyantie; Figiati Indra Dewi (University of Kuningan, 2019)
Lenong Betawi is one of community theatrical performance that still exists. It has a significant role in criticizing current social life. This paper aims to find Leech’s politeness principle in the Lenong Betawi humorous dialogue entitled “Anak Durhaka.” A story staged by Sanggar Surya Kencana group and held by Betawi Culture Institute. The method used was a content analysis by using politeness principle of Leech. The percentage results of fulfillment politeness maxims obtained 12.28% for agreement maxim, 10.52% for tact maxim, 8.11% for sympathy maxim, 2.41% for generosity maxim, 1.97% for approbation maxim, and 0.87% for modesty maxim. It means that agreement maxim as the highest and modesty maxim as the lowest fulfillment politeness maxims in Lenong Betawi humorous dialogue. Meanwhile, the percentage results of violation politeness maxims obtained 9.21% for agreement maxim, 2.63% for tact maxim, 13.81% for sympathy maxim, 4.16% for generosity maxim, 20.83% for approbation maxim, and 13.15% for modesty maxim. It means approbation maxim as the highest and tact maxim as the lowest violation politeness maxims in Lenong Betawi humorous dialogue. Finally, it can be concluded that the violation politeness maxims is more found than fulfillment politeness maxims in Lenong Betawi humorous dialogue entitled “Anak Durhaka.”